Biomimetic sonodynamic therapy-nanovaccine integration platform potentiates Anti-PD-1 therapy in hypoxic tumors. (June 2021) - Zhan, Guiting; Xu, Qingbo; Zhang, Zelong; Wei, Zhaohan; Yong, Tuying; Bie, Nana; Zhang, Xiaoqiong; Li, Xin; Li, Jianye; Gan, Lu; Yang, Xiangliang
Highlights: cMn-MOF@CM is developed for potentiating anti-PD-1 therapy in hypoxic tumors. cMn-MOF@CM generates strong SDT effects in hypoxic tumors, inducing ICD and subsequent DC maturation and T cell activation. cMn-MOF@CM as the nanovaccine directly induces DC maturation and T cell activation. Combination of cMn-MOF@CM upon US irradiation with anti-PD-1 antibody generates a long-term immunological memory function. Graphical Abstract: A biomimetic sonodynamic therapy (SDT)-nanovaccine integration platform (cMn-MOF@CM) is fabricated for enhanced antitumor immunity by tumor-associated antigens both in situ derived from SDT and OVA and the immune adjuvant CpG. The combination of cMn-MOF@CM -triggered SDT and anti-PD-1 antibody induces stronger systemic immune response and long-term immunological memory function to prevent tumor growth and recurrence. ga1 Abstract: Immune checkpoint blockade (ICB) therapy has emerged as novel therapeutic modality for hard-to-treat solid tumors. However, inadequate T cell infiltration in hypoxic solid tumors limits its anticancer efficacy. Here we develop a sonodynamic therapy (SDT)-nanovaccine integration platform constructed by binding a manganese porphyrin-based metal-organic frameworks (Mn-MOF) with an immune adjuvant CpG and then coating with cell membranes derived from ovalbumin (OVA)-overexpressing melanoma B16 cells (cMn-MOF@CM) for potentiating anti-programmed death receptor 1 (PD-1) antibody in malignant melanoma therapy. cMn-MOF@CM with prolonged blood circulation and enhanced tumor targeting efficiently relieves tumor hypoxia and generates strong SDT effects and immunogenic cell death. The tumor-associated antigens both in situ derived from SDT and OVA exhibit vaccine-like functions together with the immune adjuvant CpG, eliciting a strong tumor-specific immune response by promoting DC maturation and T cell activation. Importantly, the combination of cMn-MOF@CM-triggered SDT and anti-PD-1 antibody induces stronger systemic immune response and long-term immunological memory function to prevent tumor growth and recurrence. These findings reveal that cMn-MOF@CM with US irradiation may be a potential candidate to potentiate ICB therapy for hypoxic cancer therapy.